Tārīkh-i Kishīk Khāna-yi Humāyūn - Kāshānī, Nūr al-Dīn, (Miras Maktoob, ISBN: 9789004365452., 2019)
Abu ʼl-Muẓaffar Awrangzīb (r. 1068-1118/1658-1707), the last of the great Mughal emperors, reigned over all but the entire Indian subcontinent. His sons, in charge of individual provinces, sometimes rebelled against him. An example of this is the rebellion of Prince Akbar (d. 1116/1704) in 1091/1680-81. This revolt must have been the more disappointing to Awrangzīb as Akbar was his favourite son. However this may be, the scheme was foiled and Akbar fled to Kandahar. When he understood that there was no chance of return, Akbar eventually sought refuge with the Safavid emperor Sulaymān I (r. 1076-1105/1666-94) in Isfahan. While in Isfahan, Akbar had several people taking turns spending the day in his company. The writer of the present memoirs, the poet laureate Nūr al-Dīn Kāshānī (d. 1123/1711) was one of them. Written in 1110/1698 in Mashhad after Akbar's expulsion from Isfahan, these memoirs offer a compressed account that is both historical and anecdotal.